2011
DOI: 10.1016/j.juro.2011.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Selective Arterial Embolization for Pseudoaneurysms and Arteriovenous Fistula of Renal Artery Branches Following Partial Nephrectomy

Abstract: Pseudoaneurysms and arteriovenous fistulas of the renal artery are rare complications of partial nephrectomy. Presentation is often delayed. Superselective coil embolization is a safe, minimally invasive treatment option that usually solves the clinical problem and preserves renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
68
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 29 publications
8
68
1
2
Order By: Relevance
“…When the PA becomes larger and blood leakage occurs into the collecting system, macroscopic hematuria may occur (26). In the literature, macroscopic hematuria and/or flank pain were reported in almost all cases with PA (25,27). In line with previously reported studies, all patients were symptomatic in the present series.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…When the PA becomes larger and blood leakage occurs into the collecting system, macroscopic hematuria may occur (26). In the literature, macroscopic hematuria and/or flank pain were reported in almost all cases with PA (25,27). In line with previously reported studies, all patients were symptomatic in the present series.…”
Section: Discussionsupporting
confidence: 88%
“…In the literature, PA rate was about 0.43% for open partial nephrectomy (4) and 1.7% for laparoscopic partial nephrectomy (3). Ghoneim et al (25) reported their complication rates as 0.6% for open partial nephrectomy and 2.6% for laparoscopic partial nephrectomy. In a multicenter study of 998 patients who underwent minimally invasive partial nephrectomy, Hyams et al (1) found the frequency of iatrogenic vascular lesions and PA as 2% and 1.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations